Political Connections, Business Groups and Innovation in Asia - Simon Commander; Saul Estrin; Thamashi De Silva (Comparative Economic Studies, 2023)
It is acknowledged that Asia's remarkable economic achievements of the past 50 years build on institutional arrangements very different from the West, including the central role of business groups (BGs) as an organisational form. As the Asian economies move from extensive to intensive growth, we enquire whether the BG format will be as effective going forward, especially with respect to innovation. We argue that the ubiquity of BGs in Asia has been associated with the accretion of significant market power, as well as high overall concentration in the economy as a whole. Our empirical work draws on a sample of more than 9000 Asian firms across seven countries. We find that, unsurprisingly, given their access to additional resources, BGs are more innovative than non-affiliates. However we also find that the wider consequences of the BG form for innovation may be negative.
Keywords: L22; O30; O53; 330; Innovation; R&D; Asian business groups; Market power; Overall concentration